2017
DOI: 10.3390/ijms18020473
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights into Long Non-Coding RNAs (LncRNAs) in Prostate Cancer

Abstract: The importance of long non-coding RNAs (lncRNAs) in the pathogenesis of various malignancies has been uncovered over the last few years. Their dysregulation often contributes to or is a result of tumour progression. In prostate cancer, the most common malignancy in men, lncRNAs can promote castration resistance, cell proliferation, invasion, and metastatic spread. Expression patterns of lncRNAs often change during tumour progression; their expression levels may constantly rise (e.g., HOX transcript antisense R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 89 publications
1
58
0
Order By: Relevance
“…6,7 A large number of studies have shown that lncRNAs can affect the progression of many types of tumor. [8][9][10] For example, lncRNA OR3A4 promotes the growth, invasion and metastasis of gastric cancer by up-regulating the expression of guaninenucleotide-binding protein beta polypeptide 2-like 1; 11 the up-regulated expression of lncRNA ZFAS1 is associated with the epithelial-mesenchymal transition (EMT) of breast cancer cells; 12 and lncRNA HCAL, as ceRNA of lysosomal-associated transmembrane protein 4B, promotes the growth and metastasis of HCC. 13 In addition, studies have shown that EGOT promotes the development and progression of gastric cancer; 14 and it is a lncRNA induced by HCV infection, and increases viral replication by counteracting antiviral responses.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 A large number of studies have shown that lncRNAs can affect the progression of many types of tumor. [8][9][10] For example, lncRNA OR3A4 promotes the growth, invasion and metastasis of gastric cancer by up-regulating the expression of guaninenucleotide-binding protein beta polypeptide 2-like 1; 11 the up-regulated expression of lncRNA ZFAS1 is associated with the epithelial-mesenchymal transition (EMT) of breast cancer cells; 12 and lncRNA HCAL, as ceRNA of lysosomal-associated transmembrane protein 4B, promotes the growth and metastasis of HCC. 13 In addition, studies have shown that EGOT promotes the development and progression of gastric cancer; 14 and it is a lncRNA induced by HCV infection, and increases viral replication by counteracting antiviral responses.…”
Section: Introductionmentioning
confidence: 99%
“…5 It has been wildly investigated that lncRNAs modulate many types of tumor progression. [6][7][8] For example, lncRNA LOC100129148 and EWSAT1 have been reported to act as oncogenic role in nasopharyngeal carcinoma, 9,10 lncRNA 00858 functions as a competing endogenous RNA for miR-422a to facilitate the cell growth in non-small cell lung cancer 11 and Increased expression of long-noncoding RNA ZFAS1 is associated with epithelial-mesenchymal transition of gastric cancer. 12 It also has been reported that high DLX6-AS1 expression levels were significantly associated with both histological differentiation and TNM stage of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Figures[6][7][8]. Generally speaking, EMT of tumour cells occurred with fading away of inter-cellular junctions, and incredible invasion and migration of tumour cells, so it has been deemed as a major step inherent in tumour development and migration.…”
mentioning
confidence: 99%